Transdisciplinary perspectives on risk management and cyber intelligence - Dall'Acqua, Luisa, 1962-; Gironacci, Irene M., 1988- (Advances in information security, privacy, and ethics (AISPE) book series., 2021)
"This book explores perspectives and approaches to the intelligence analysis and risk management"--